Measuring User Satisfaction in Academic Libraries - Koovakkai, Dineshan (Journal of Information and Knowledge, 2008)
Satisfying the users is the prime concern of every modern library. Hence it is mandatory on the part of the libraries to measure the satisfaction of the users in order to provide better services. To measure the user satisfaction, standardised and appropriate tools are necessary. The author is reporting the user satisfaction scale developed by him for measuring the user satisfaction of academic libraries. The scale can be adapted and used for measuring user satisfaction in other types of libraries as well.